A water-based zinc ion battery double-salt electrolyte system with corrosion resistance to aluminum foil current collector

CN122931086APending Publication Date: 2026-10-16ADVANCED TECH RES INST OF BEIJING UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510431389.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-08
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但是随着盐的浓度增加,电解液成本、粘度等会急剧增加,同时电导率也随之下降,动力学减慢

Benefits of technology

[0027] (1) The electrolyte of the present invention uses a mixture of organic zinc salt and organic lithium salt to compete, and the hydrogen bond interaction between the fluorine functional group and water restricts most of the water in the solvation shell, thereby significantly reducing the activity of water and thus reducing the corrosion of aluminum foil in the water environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005348280920000011
    Figure HDA0005348280920000011
  • Figure HDA0005348280920000012
    Figure HDA0005348280920000012
  • Figure HDA0005348280920000021
    Figure HDA0005348280920000021
Patent Text Reader

Abstract

The present application relates to the application of aluminum foil current collector in water-based zinc ion battery in the field of new energy material technology. By constructing a double-salt electrolyte, the concentration of one salt is moderately regulated, and a stable electrolyte environment is constructed. The system constructs an ion-rich and water-poor solvent shell, promotes the arrival of ions to the electrode surface, and helps the aluminum foil current collector surface to form a stable solid-state electrolyte interface (SEI), preventing further corrosion of the current collector. In addition, a small amount of free water corrodes the aluminum foil during the initial charging process while contributing to the capacity, improving the battery life. Compared with other current collectors, the density and thickness of the aluminum foil are reduced, further improving the energy density of the battery. In summary, the electrolyte effectively inhibits the corrosion of the aluminum foil current collector in the water-based electrolyte, successfully applies the aluminum foil with advantages in weight, electrical conductivity, mechanical strength and cost-effectiveness in water-based zinc battery. This technology can be popularized to various water-based batteries in the future to promote the development of high-energy-density water-based batteries, showing good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a dual-salt electrolyte system for aqueous zinc-ion batteries that is corrosion-resistant to aluminum foil current collectors, and belongs to the field of aqueous zinc-ion battery technology. Background Technology

[0002] As the mainstream technology in current electrochemical energy storage systems, lithium-ion batteries maintain a dominant position in the commercial field due to their dual high characteristics (high specific energy and high cycle stability). However, the resource constraints of strategic lithium metal lead to increasingly severe supply bottlenecks. More critically, the uncontrollable dendrite growth mechanism of lithium metal anodes can trigger a thermal runaway chain reaction through micro-electrode penetration, resulting in violent vaporization and deflagration of highly active organic electrolyte systems, posing a serious public safety risk.

[0003] As a promising new energy storage system, aqueous zinc-ion batteries have been established as a strong candidate for next-generation energy storage systems due to their intrinsic safety characteristics and excellent power performance. In comparison, zinc metal anodes exhibit significant material advantages: they combine the resource advantages of natural abundance, cost controllability, and ecological compatibility, offering disruptive innovation value compared to traditional lithium-based materials. Research on the positive electrode current collector in aqueous batteries, while not immediately apparent, is a crucial but still widely addressed issue. The strong corrosion of metals and the water decomposition sensitivity of aqueous electrolytes necessitate that current collectors possess both high conductivity and low hydrolysis catalytic properties. Currently, only stainless steel, titanium, and carbon-based materials have been applied, but their high density and cost lead to large system space requirements and pose chemical / electrochemical corrosion risks, significantly limiting improvements in battery mass / volume energy density and long-term stability. Aluminum foil current collectors, due to their lightweight, low cost, and high conductivity, are the best candidate material for current collectors; however, their instability and susceptibility to corrosion in aqueous environments remain significant challenges.

[0004] To address these issues, the research team conducted studies on surface coatings and electrolyte regulation. For example, magnetron sputtering of niobium coatings acts as a barrier against aggressive substances, while the Al-Nb foil, used as the negative electrode current collector, also inhibits the formation of passivation products and regulates zinc deposition. (B. Liu, T. Lv, A. Zhou, X. Zhu, Z. Lin, T. Lin, L. Suo, Aluminum corrosion–passivation regulation prolongs aqueous batteries life, Nat. Commun. 2024, 15) Another strategy involves using anti-corrosion additives to regulate aluminum corrosion and extend the cycle life of aqueous batteries. By introducing hydrolytic anionic additives (HTAs) such as lithium carbonate and lithium phosphate to catalyze the formation of aluminum hydroxide passivation layers from aluminum metal corrosion, covering corrosion sites, further corrosion of aluminum is inhibited (R. Zhu, Z. Xiong, H. Yang, N. Wang, S. Kitano, C. Zhu, Y. Aoki, H. Habazaki, Anode / Cathode Dual-Purpose Aluminum Current Collectors for Aqueous Zinc-Ion Batteries, Adv. Funct. Mater. 2022, 33). These strategies provide excellent solutions for the application of aluminum foil in aqueous batteries. In electrolyte control schemes, in-depth research on high-concentration aqueous electrolytes (such as using 21m "Water-in-salt" electrolytes) has revealed that the electrolyte can spontaneously form an SEI film during charge and discharge, while also widening the electrochemical window, significantly improving the cycle life of aqueous batteries. However, as the salt concentration increases, the cost and viscosity of the electrolyte increase dramatically, while the conductivity decreases and the kinetics slow down. Therefore, regulating the electrolyte formulation and ratio to ensure the stable presence of aluminum foil in aqueous batteries has significant research implications. Summary of the Invention

[0005] The purpose of this invention is to provide a water-based zinc-ion battery dual-salt electrolyte system that is corrosion-resistant to aluminum foil current collectors.

[0006] The dual-salt electrolyte in the aqueous zinc-ion battery prepared in this invention is mainly obtained by mixing organic zinc salt, organic lithium salt, and water. This invention proposes an electrolyte constructed using a competitive mechanism of dual ions at appropriate concentrations. This electrolyte confines most water molecules within an ion-solubilized shell, effectively suppressing H2O activity and thus protecting the aluminum foil current collector. By controlling the lithium salt concentration, the attack of some free active water on the aluminum foil is utilized, providing some capacity while forming an inorganic LiF-rich SEI protective layer to prevent further corrosion. This study successfully applies aluminum foil to aqueous zinc batteries, effectively improving the battery's energy density. The preparation method of the aqueous electrolyte described in this invention is simple, easy to operate, environmentally friendly, uses readily available raw materials, and is easy to promote.

[0007] The objective of this invention is achieved through the following technical solutions.

[0008] The present invention provides a dual-salt electrolyte, which is made by mixing an organic zinc salt, an organic lithium salt and water.

[0009] In the electrolyte described above, the zinc salt is selected from one of the organic zinc salts Zn(CF3SO3)2 and Zn(TFSI)2.

[0010] In the electrolyte described above, the lithium salt is selected from one of the organic lithium salts LiCF3SO3, LiTFSI, LiN(SO2CF3)2, and LiC(SO2CF3)3.

[0011] In this invention, the organic salt is a fluorine-containing organic compound that can form a LiF interface protective layer on the surface of aluminum foil in an aqueous environment.

[0012] In the electrolytes described above, both salts have high solubility in water and can form a homogeneous electrolyte.

[0013] The method for preparing the electrolyte provided by the present invention includes the following steps:

[0014] (1) In an inert atmosphere, zinc salt and lithium salt are prepared separately in a certain proportion.

[0015] (2) Dissolve the prepared salts in water in sequence, mix and stir evenly to obtain a water-double salt mixed electrolyte.

[0016] In the above preparation method, the inert atmosphere is nitrogen or argon with a purity of not less than 99% (or with an O2 content of <1ppm).

[0017] In the above-mentioned electrolyte, the molar concentration of zinc salt dissolved in water can be 0.01–25 mol / L; the molar concentration of lithium salt dissolved in water can be 0.01–25 mol / L.

[0018] The research on the application of the dual-salt electrolyte of this invention to corrosion-resistant aluminum foil current collectors in aqueous zinc-ion batteries can be extended to other aqueous battery fields such as aqueous lithium-ion batteries.

[0019] In the above applications, the aqueous zinc-ion battery system is LiMn2O4-Zn, LiFePO4-Zn, or LiNi. 0.5 Mn 1.5 O4-Zn zinc-ion battery system.

[0020] In the above applications, the application of the anti-corrosion aluminum foil current collector in a dual-salt electrolyte environment, the ambient temperature for electrolyte and full cell testing is -40℃ to 30℃.

[0021] This invention further provides an aqueous zinc-ion battery dual-salt electrolyte system with corrosion resistance to aluminum foil current collectors, mainly used in aqueous zinc-ion batteries, including a positive electrode, a negative electrode and an electrolyte;

[0022] The active material of the positive electrode is LiMn2O4, LiFePO4, or LiNi. 0.5 Mn 1.5 O4, the active material of the negative electrode is metallic zinc (Zn);

[0023] The electrolyte is the aqueous zinc-ion battery dual-salt electrolyte described above.

[0024] In the above-mentioned aqueous zinc-ion batteries, the ambient temperature for testing the entire battery can be -40 to 30°C.

[0025] In a specific example, the assembly of the full cell of the aqueous zinc-ion battery is as follows: the electrode plates, aqueous electrolyte, gaskets, and spring contacts are sequentially placed into a 2032 button cell casing in the order of negative electrode shell - negative electrode plate - separator - electrolyte - positive electrode plate - gasket - spring contact - positive electrode shell to assemble a full cell. Then, the cell is pressed into a button cell using a pressing machine. The thickness of the gasket is 1 mm, and the separator is made of glass fiber GF / D.

[0026] The present invention has the following advantages:

[0027] (1) The electrolyte of the present invention uses a mixture of organic zinc salt and organic lithium salt to compete, and the hydrogen bond interaction between the fluorine functional group and water restricts most of the water in the solvation shell, thereby significantly reducing the activity of water and thus reducing the corrosion of aluminum foil in the water environment.

[0028] (2) With appropriate electrolyte concentration, the attack of some free active water on the aluminum foil provides some capacity while forming an SEI protective layer rich in inorganic LiF, which prevents further corrosion and improves the battery cycle life.

[0029] (3) The preparation method of the aqueous electrolyte described in this invention is simple, easy to operate, environmentally friendly, and uses readily available raw materials, making it easy to promote. Furthermore, compared to other current collectors, the density and thickness of the aluminum foil are reduced, further improving the battery energy density. Attached Figure Description

[0030] Figure 1 Cyclic chronocurrent tests were conducted on the mixed liquid electrolytes prepared in Example 2 and Comparative Example 1.

[0031] Figure 2 The image shows a SEM image of the mixed liquid electrolyte prepared in Comparative Example 1 after corrosion testing.

[0032] Figure 3 The image shows a SEM image of the mixed liquid electrolyte prepared in Example 1 after corrosion testing.

[0033] Figure 4 The graph shows the data from ICP-OES / MS testing of the electrolytes taken after testing in Example 1 and Comparative Example 1.

[0034] Figure 5 The cycle capacity-coulombic efficiency diagram of the full cell assembled with the mixed liquid electrolyte prepared in Example 2 and Comparative Example 1 at 30°C.

[0035] Figure 6 The mass spectra (DEMS) of oxygen changes during the first two weeks of charging and discharging of the full cells assembled with the mixed liquid electrolytes prepared in Example 2 and Comparative Example 4 are shown.

[0036] Figure 7 XPS image of the aluminum foil surface prepared in Example 2. Detailed Implementation

[0037] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. Unless otherwise specified, the methods described are conventional methods, and the raw materials described are available from publicly available commercial sources.

[0038] In the following embodiments:

[0039] SEM testing: The microstructure of the negative electrode material before and after cycling was observed using a field emission scanning electron microscope (FEI, Quanata 200f) with an accelerating voltage of 20kV.

[0040] Assembly of CR2032 button cell: The electrode plates, aqueous electrolyte, gaskets, and spring contacts are placed into the CR2032 button cell casing in the following order: negative electrode shell - negative electrode plate - separator - electrolyte - positive electrode plate - gasket - spring contact - positive electrode shell. The cells are then assembled into a complete cell. The cells are then pressed together using a pressing machine to obtain the button cell. The gaskets are 1 mm thick, and the separator is made of glass fiber GF / D.

[0041] Electrochemical performance testing: The assembled CR2032 button batteries were electrochemically tested using a Newway battery tester, and the charge-discharge curves were recorded by software; the chronoampere current was tested on an electrochemical workstation (lvium-Start, lvium-N-Stat, Netherlands), with an applied voltage of 1.35V; the gas production of the battery was analyzed using an electrochemical mass spectrometer (Hiden PHR20, Beijing Engelde Analytical Technology Co., Ltd.).

[0042] Example 1:

[0043] In a glove box filled with argon gas of ≥99% purity, weigh out 1 mol / L Zn(CF3SO3)2:10 mol / LiTFSI, take out the mixture and mix it with the corresponding amount of ultrapure water, and stir it thoroughly for 12 hours to obtain a mixed electrolyte.

[0044] The CA corrosion current of the mixed liquid electrolyte prepared in this embodiment was tested using an Lvium-Start electrochemical workstation with a three-electrode system. The reference electrode was an Ag / AgCl electrode, the applied voltage was 1.35V, the time was 540s, and the cycle was 10 times. The test results show that the aqueous electrolyte of this invention achieves good corrosion resistance of aluminum foil in the electrolyte.

[0045] Example 2:

[0046] Based on Example 1, except that the organic zinc salt is replaced with Zn(TFSI)2, all other steps and conditions are the same as in Example 1, and a mixed electrolyte is obtained accordingly.

[0047] The CA corrosion current of the mixed liquid electrolyte prepared in this embodiment was tested using an Lvium-Start electrochemical workstation with a three-electrode system. The reference electrode was an Ag / AgCl electrode. The applied voltage was 1.35V, the time was 540s, and the cycle was 10 times. The test results show (e.g.) Figure 1 The aqueous electrolyte of this invention significantly reduced the corrosion current density of the aluminum foil in the electrolyte compared to Comparative Example 1, demonstrating satisfactory corrosion resistance. XPS testing after removing the aluminum foil confirmed the formation of a corrosion-resistant LiF interface layer on its surface.

[0048] Example 3:

[0049] The aluminum foil from Example 2 was removed and its appearance morphology was analyzed. For example... Figure 3 As shown, the surface of the aluminum foil under this electrolyte ratio shows almost no obvious change, proving that the surface of the aluminum foil is flat and can exist stably under this environment.

[0050] Example 4:

[0051] After removing the aluminum foil from Example 2, the electrolyte was collected and analyzed using inductively coupled plasma optical emission spectrometry (ICP-OES / MS) to determine the aluminum content in the electrolyte after etching. Figure 4 As shown, the aluminum foil with this electrolyte ratio is hardly corroded by the electrolyte, and the element content of the electrolyte is only 0.33 ppm.

[0052] Example 5:

[0053] Button batteries were assembled according to the electrolyte formulation in Example 2, using a CR2032 battery case, with 12mm diameter pure zinc foil as the negative electrode, a glass fiber separator, and LFP as the positive electrode, to form a full cell. Testing was conducted at 30°C using a Newway electrochemical testing system, with the assembled full cell tested at a 1C rate. The amount of active material was calculated. Figure 5 As shown, after 800 cycles, the full cell in this embodiment exhibits slow capacity decay and stable coulombic efficiency without significant fluctuations, proving that the aluminum foil current collector can exist stably in this aquatic environment.

[0054] Comparative Example 1:

[0055] In a glove box filled with argon gas of ≥99% purity, the following mixture was weighed according to the ratio of 1 mol / L Zn(TFSI)2:2 mol / LiTFSI, taken out and mixed with the corresponding amount of ultrapure water, and stirred thoroughly for 12 h to obtain a mixed electrolyte;

[0056] The CA corrosion current of the mixed liquid electrolyte prepared in this comparative example was tested using an Lvium-Start electrochemical workstation with a three-electrode system. The reference electrode was an Ag / AgCl electrode, and the applied voltage was 1.35V for 540s, with 10 cycles. The test results showed... Figure 1 The corrosion current under this electrolyte ratio is much higher than that in Example 2, indicating that the aluminum foil is severely corroded in this electrolyte.

[0057] Comparative Example 2: The aluminum foil from Comparative Example 1 was removed and its appearance morphology was analyzed. For example... Figure 2 As shown, the aluminum foil surface under this electrolyte ratio is severely cracked and pitted, with obvious corrosion marks, further proving that the aluminum foil cannot be protected under this environment.

[0058] Comparative Example 3:

[0059] After removing the aluminum foil from Comparative Example 1, the electrolyte was collected and analyzed using inductively coupled plasma optical emission spectrometry (ICP-OES / MS) to determine the aluminum content in the electrolyte after etching. Figure 4As shown, the element content of the electrolyte was as high as 5.934 ppm, indicating that most of the aluminum foil was dissolved in the electrolyte, and the system was severely corroded.

[0060] Comparative Example 4:

[0061] In a glove box filled with argon gas of ≥99% purity, weigh out 1 mol / L Zn(CF3SO3)2: 2 mol / Li(CF3SO3)2, take it out and mix it with the corresponding amount of ultrapure water, and stir it thoroughly for 12 hours to obtain a mixed electrolyte.

[0062] The mixed liquid electrolyte prepared in this comparative example was assembled into a full cell with LiMn2O4 positive electrode and Zn negative electrode in an electrochemical reaction cell, and the results were analyzed using a Hiden PHR20 electrochemical mass spectrometer. Figure 6 It can be seen that a large amount of oxygen was generated during the first two weeks of charging and discharging of the full battery LiMn2O4-Zn prepared by the mixed liquid electrolyte of the present invention, indicating that the decomposition and corrosion of aluminum foil in the mixed liquid electrolyte prepared in the comparative example was not effectively suppressed.

[0063] In summary, the above are merely preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A water-based zinc-ion battery dual-salt electrolyte system with corrosion resistance to aluminum foil current collectors, characterized in that: The aqueous electrolyte is a dual-salt electrolyte obtained by mixing zinc salt, lithium salt and water. It has a low-activity water environment of "salt-enclosed water" and excellent electrochemical stability.

2. The dual-salt electrolyte according to claim 1, characterized in that: The zinc salt is one of the organic zinc salts Zn(CF3SO3)2 and Zn(TFSI)2.

3. The dual-salt electrolyte according to claim 1, characterized in that: The lithium salt is one of the organic lithium salts LiCF3SO3, LiTFSI, LiN(SO2CF3)2, and LiC(SO2CF3)3.

4. The dual-salt electrolyte according to claim 1, characterized in that: The organic salt is a fluorine-containing organic compound that can form an interfacial protective layer on the surface of aluminum foil in an aqueous environment.

5. The dual-salt electrolyte according to claim 1, characterized in that: Both salts have high solubility in water and can form a homogeneous electrolyte.

6. A method for preparing a dual-salt electrolyte as described in any one of claims 1 to 5, characterized in that: The method steps are as follows: (1) In a glove box filled with protective gas, zinc salt and lithium salt are prepared in a certain proportion respectively; (2) Take out the salt prepared above, dissolve it in water in the air in sequence, mix and stir evenly to obtain water-double salt mixed electrolyte; The protective gas is nitrogen or argon with a purity of not less than 99%.

7. The method for preparing the dual-salt electrolyte according to claim 6, characterized in that: In this electrolyte, the molar concentration of zinc salt dissolved in water can be 0.01–25 mol / L; the molar concentration of lithium salt dissolved in water can be 0.01–25 mol / L.

8. A water-based zinc-ion battery dual-salt electrolyte system with corrosion resistance to aluminum foil current collectors as described in claims 1-5, characterized in that: The dual-salt electrolyte is used as an electrolyte in the aluminum foil current collector system of aqueous zinc-ion batteries to generate a stable anti-corrosion interface layer, and can be extended to other aqueous battery fields.

9. The aqueous zinc-ion battery dual-salt electrolyte system with corrosion resistance to aluminum foil current collectors according to claim 7, characterized in that: The aqueous zinc-ion battery system is LiMn2O4-Zn, LiFePO4-Zn, or LiNi. 0.5 Mn 1.5 O4-Zn zinc-ion battery system.

10. The aqueous zinc-ion battery dual-salt electrolyte system with corrosion resistance to aluminum foil current collectors as described in claim 8, wherein the ambient temperature for electrolyte and full cell testing is -40℃ to 30℃.